Gender-Based Violence Against Polygamy Women (Ethnomethodology Study on Polygamous Families in Lubuk Durian Village, Kerkap District, North Bengkulu Regency) - Sri Narti; Anis Endang SM (IHSA Institute, 2022)
The phenomenon of gender-based violence in the household is an interesting issue to study, one of which is polygamy. The research objective is to examine the processes and forms of verbal and nonverbal violence, front stage backstage in social interaction so that polygamy causes violence against women. The research was conducted because census data on polygamous wives experienced an increase in violence. The urgency of this to look at the psychosocial impacts of gender-based violence on the pattern of relations in the social system such as the economic impact. Ethnomethodology as a daily practice is classified as a qualitative research focuses on the actions of actors who are considered a norm. The results of the study found that the process of verbal and nonverbal violence occurred before and after polygamy. Forms of verbal violence include husbands arguing, always criticizing, threatening, ignoring the wife's presence, accusing and blaming with bad names, manipulating, embarrassing their wives, ridiculing, and insulting. His nonverbal violence was hitting and slapping. In the front stage, the wife looks strong, patient, and happy, while the backstage is the opposite. Polygamy causes violence against women because the practice of polygamy does not meet the requirements for polygamy either according to Islamic law and the polygamy law. The presence of regulations on polygamy is not fully binding and refers to the principle of marriage. The implication is that the rules on polygamy are considered not yet realized so it is necessary to review the Law on Polygamy and its derivatives.